Rogues in the gallery : the modern plague of art thefts - McLeave, Hugh (Boson Books, 2003)
ROGUES IN THE GALLERY exposes it all: the cozy insurance ransom racket, the professional gangs of art thieves, the specialists, the connections with the international drug racket and the Mafia. Hugh McLeave has researched the whys and wherefores of the question for years, drawing on resources available to him through agencies such as Interpol, the FBI, the French, and Scotland Yard.